2017
DOI: 10.1155/2017/1295038
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to ChronicToxoplasma gondiiInfection Induced by a DNA Vaccine Expressing GRA16

Abstract: Toxoplasma gondii can infect all warm-blooded animals including human beings. T. gondii dense granule protein 16 (TgGRA16) as a crucial virulence factor could modulate the host gene expression. Here, a DNA vaccine expressing TgGRA16 was constructed to explore the protective efficacy against T. gondii infection in Kunming mice. The immune responses induced by pVAX-GRA16 were also evaluated. Mice immunized with pVAX-GRA16 could elicit higher levels of specific IgG antibody and strong cellular response compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…In this study, a significantly higher level of splenocyte proliferative response was induced by DNA immunization with pDsRed2-GRA8. This result was similar to those of previous studies reporting that DNA vaccination with GRA7 and GRA16 could increase splenocyte proliferation compared with that in controls [ 25 , 26 ]. These results suggest that a cellular immune response was elicited in the immunized mice.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, a significantly higher level of splenocyte proliferative response was induced by DNA immunization with pDsRed2-GRA8. This result was similar to those of previous studies reporting that DNA vaccination with GRA7 and GRA16 could increase splenocyte proliferation compared with that in controls [ 25 , 26 ]. These results suggest that a cellular immune response was elicited in the immunized mice.…”
Section: Discussionsupporting
confidence: 92%
“…The vaccine candidate antigens involved in protective immunity against T. gondii include membrane-associated surface antigens (SAGs) and secreted GRAs, MICs and ROPs [ 16 24 ]. However, none of these antigens could completely inhibit tissue cyst formation [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Immunization with a DNA vaccine encoding T. gondii superoxide dismutase (TgSOD) could trigger strong humoral and cellular immune responses, and had a significant increase in the survival days (median survival of 12.5 days) in comparison to the control groups against acute T. gondii ME49 strain infection in the BALB/c mice ( 52 ). Another study showed the Kunming mice immunized with pVAX-GRA16 could slightly prolong the survival time (8.4 ± 0.78 days, p > 0.05) and significantly decrease brain cysts (43.89%, p < 0.05) compared to those in all the controls ( 53 ). The survival time in BALB/c mice vaccinated with pSAG4 (9.3 ± 1.64 days) was longer than that of the mice injected by PBS or nothing after virulent T. gondii RH strain challenge.…”
Section: Discussionmentioning
confidence: 98%
“…In previous studies, some DNA vaccine candidates encoding GRA protein of T. gondii , such as GRA6, GRA7, GRA2, GRA15, GRA16, GRA24, and GRA25, have demonstrated some efficacy against T. gondii infection, with their ability of eliciting immunity, particularly cellular immune responses, which is critical for defending against acute and chronic toxoplasmosis in animal models ( Chen et al, 2015 ; Hu et al, 2017 ; Xu et al, 2019 ; Zheng et al, 2019 ). In the present study, we constructed a DNA vaccine expressing TgGRA39, and evaluated its immunogenicity and protective efficacy against infection with the highly virulent T. gondii RH strain and the chronic T. gondii PRU strain.…”
Section: Discussionmentioning
confidence: 99%